Gyrokinetic simulation of low-n Alfvénic modes in tokamak HL-2A plasmas. (1st January 2023) - Lin 林, Wen-Hao 文浩; Li 李, Ji-Quan 继全; Garcia, J; Mazzi, S
Abstract : The turbulence characteristics of plasmas with internal transport barriers in the HL-2A tokamak are analyzed by means of linear gyrokinetic simulations. It is found that turbulence is dominated by the ion temperature gradient (ITG) mode together with large-scale modes characterized by high-frequency electromagnetic fluctuation, which are destabilized by the steep ion temperature gradient in the weak magnetic shear regime. Comparison with solutions of analytical dispersion relations shows that their linear features match well with the beta-induced Alfvén eigenmode branch of the shear Alfvénic spectrum. It is further clarified that the large population of fast ions in these plasmas plays a stabilization role through the dilution mechanism in high- n ITG mode regimes.